HIGH-RESOLUTION SPECTROSCOPIC OBSERVATIONS OF BINARY STARS AND YELLOW STRAGGLERS IN THREE OPEN CLUSTERS : NGC 2360, NGC 3680, AND NGC 5822 - SILVA, J V SALES; SUAREZ, V J PENA; SANTRICH, O J KATIME; Pereira, C B; Drake, N A; Roig, F (The Astronomical journal, 2014)
Binary stars in open clusters are very useful targets in constraining the nucleosynthesis process. The luminosities of the stars are known because the distances of the clusters are also known, so chemical peculiarities can be linked directly to the evolutionary status of a star. We carried out a detailed spectroscopic analysis to derive the atmospheric parameters for 16 red giants in binary systems and the chemical composition of 11 of them in the open clusters NGC 2360, NGC 3680, and NGC 5822. We obtained abundances of C, N, O, Na, Mg, Al, Ca, Si, Ti, Ni, Cr, Y, Zr, La, Ce, and Nd. The atmospheric parameters of the studied stars and their chemical abundances were determined using high-resolution optical spectroscopy. We employ the local thermodynamic equilibrium model atmospheres of Kurucz and the spectral analysis code moog. The abundances of the light elements were derived using the spectral synthesis technique. Finally, rotational velocities were also determined and their values were compared with those already determined for field giant stars.